PELAKSANAAN RESTITUSI BAGI ANAK YANG MENJADI KORBAN TINDAK PIDANA SEBAGAI BENTUK PEMBARUAN HUKUM PIDANA BERDASARKAN PERATURAN PEMERINTAH NOMOR 43 TAHUN 2017 - Putri, Miszuarty (Soumatera Law Review, 2019)
One of the issues that is of concern to the government, experts and the public is that rape cases, especially rape crimes committed by adults to underage children, have lately caused a reaction among the community due to dissatisfaction with the criminal community dropped on the perpetrator, based on legal knowledge, the victim can claim damages / compensation or restitution to the convicted person. The problem approach method used is normative jurid, namely the law approach that is carried out on the Government Regulation of the Republic of Indonesia Number 43 Year 2017. The results of the study show that the Government Regulation of the Republic of Indonesia Number 43 of 2017 has provided detailed arrangements for the procedure for submitting restitution and procedures granting restitution for children who are victims of criminal acts or their heirs, but there are still shortcomings that need to be refined in this government regulation concerning substitute crimes, if my / defendant / convicted convicts implement a court decision that has permanent legal force regarding the implementation of restitution. As well as it is expected that in the future the judge's decision on the granting of this restitution can be in the form of additional criminal sanctions in addition to the principal penalty in the form of imprisonment and fine.